CONSUMERS FACING SUPRA-COMPLEX CHOICES IN THE MODERN MARKETPLACE - Torben Hansen; Thyra Uth Thomsen (European Scientific Journal, ESJ, 2014)
In this paper, we suggest that many of the choice situations confronting consumers in the modern marketplace have become supra-complex. Supra-complex decision-making occurs when the perceived difficulty of transforming product information into knowledge exceeds the expected benefits of doing so, even if decision-making heuristics, or other kind of attribute-related decision rules, are applied. Under conditions of supra-complexity, we propose that consumers instead use mental markers in order to justify their decisions. Mental markers are any mental construct the consumer uses for the purpose of gaining mental justification of overall choices. We argue that the usage of mental markers leads to reductions in cognitive dissonance, reduced usage of mental resources and time. Drawing on the principle of mental justification as well as consumers’ propensity to use goals as blueprints for directing their behaviour, we propose a framework for understanding consumer decisions when faced with supra-complexity.